2022
DOI: 10.1002/pros.24325
|View full text |Cite
|
Sign up to set email alerts
|

177Lu‐PSMA radioligand therapy effectiveness in metastatic castration‐resistant prostate cancer: An updated systematic review and meta‐analysis

Abstract: Background An updated systematic review and meta‐analysis of relevant studies to evaluate the effectiveness of prostate‐specific membrane antigen (PSMA)‐targeted endoradiotherapy/radioligand therapy (PRLT) in castration resistant prostate cancer (CRPC). Methods A systematic search was performed in July 2020 using PubMed/Medline database to update our prior systematic review. The search was limited to papers published from 2019 to June 2020. A total of 472 papers were reviewed. The studied parameters included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…As more and more academic and general hospitals in Europe are offering radiopharmaceutical therapies like [ 177 Lu]Lu-PSMA therapy (Weineisen et al 2015 ) from an in-house production, the demand for adequate quality control methods is increasing (Kratochwil et al 2019 ; Sadaghiani et al 2022 ; Kalmthout et al 2020 ). Prostate Specific Membrane Antigen (PSMA) labelled with Lu-177 is used for the treatment of metastatic Castration Resistant Prostate Cancer (mCRPC), it’s use has increased after FDA approval of [ 177 Lu]Lu-PSMA-617 (Pluvicto ® ).…”
Section: Introductionmentioning
confidence: 99%
“…As more and more academic and general hospitals in Europe are offering radiopharmaceutical therapies like [ 177 Lu]Lu-PSMA therapy (Weineisen et al 2015 ) from an in-house production, the demand for adequate quality control methods is increasing (Kratochwil et al 2019 ; Sadaghiani et al 2022 ; Kalmthout et al 2020 ). Prostate Specific Membrane Antigen (PSMA) labelled with Lu-177 is used for the treatment of metastatic Castration Resistant Prostate Cancer (mCRPC), it’s use has increased after FDA approval of [ 177 Lu]Lu-PSMA-617 (Pluvicto ® ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the study of Kind et al (1) a PSA value of >25% was considered as progression in our study. A ≥50% PSA reduction was concidered a biochemical response to treatment in several studies (21,22). A systemic review and meta-analysis of Sadaghiani et al (22) reported a PSA reduction of ≥50% after treatment in 52% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative knowledge and experience on PSMA-targeted RLT and its efficacy and safety has been accumulating over the last six years [ 1 , 2 ]. PSMA-RLT is becoming recognized as an option for advanced mCRPC patients, but optimal treatment protocols or the safety and efficacy of sequencing and combining PSMA-RLT with other treatments have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were also high-volume metastatic patients who clearly benefited from serial treatments and experienced a continuous decline of PSA. Both any decline and a ≥50% PSA response in PSMA-RLT have been shown to be linked to better OS in a meta-analysis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation